2007
DOI: 10.1094/mpmi-20-3-0293
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Genome-Wide Expression Profiling of Host and Pathogen During Soybean Cyst Nematode Infection of Soybean

Abstract: Global analysis of gene expression changes in soybean (Glycine max) and Heterodera glycines (soybean cyst nematode [SCN]) during the course of infection in a compatible interaction was performed using the Affymetrix GeneChip soybean genome array. Among 35,611 soybean transcripts monitored, we identified 429 genes that showed statistically significant differential expression between uninfected and nematode-infected root tissues. These included genes encoding enzymes involved in primary metabolism; biosynthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
192
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(204 citation statements)
references
References 54 publications
9
192
2
1
Order By: Relevance
“…PME3, therefore, plays a crucial role in cyst nematode parasitism, which also gives additional credence to the conclusion that the interaction with PME3 is of importance for the function of CBP. In addition, the soybean ortholog of PME3 (BE821923) was shown to be upregulated within the actual developing syncytia induced by the soybean cyst nematode H. glycines (Ithal et al, 2007), which provides additional evidence of a role for PME3 in the cyst nematode infection process. Most importantly, a direct functional connection between PME3 and CBP is supported by our finding that transgenic plants expressing Hs CBP exhibited higher PME activity than wild-type controls.…”
Section: Discussionmentioning
confidence: 87%
“…PME3, therefore, plays a crucial role in cyst nematode parasitism, which also gives additional credence to the conclusion that the interaction with PME3 is of importance for the function of CBP. In addition, the soybean ortholog of PME3 (BE821923) was shown to be upregulated within the actual developing syncytia induced by the soybean cyst nematode H. glycines (Ithal et al, 2007), which provides additional evidence of a role for PME3 in the cyst nematode infection process. Most importantly, a direct functional connection between PME3 and CBP is supported by our finding that transgenic plants expressing Hs CBP exhibited higher PME activity than wild-type controls.…”
Section: Discussionmentioning
confidence: 87%
“…In this report, we demonstrate that defense signaling is suppressed in root galls caused by M. graminicola very early after infection of the rice root. Transcriptome studies already suggested that JA signaling and some genes involved in JA biosynthesis are suppressed during fully established compatible cyst nematode infections in soybean (Ithal et al, 2007a(Ithal et al, , 2007b. Data from RKN giant cells in Arabidopsis (Jammes et al, 2005;Barcala et al, 2010) revealed that many defense-related genes, previously shown to be induced in other plant-pathogen interactions, like PR proteins, coding enzymes of the phenylpropanoids, salicylate signaling, cytokinin signaling, genes involved in lignin biosynthesis, simple phenols, and shikimate biosynthetic pathways, follow an overall down-regulation in galls and in giant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most research to date on host gene expression in response to RKNs has focused on interactions in dicotyledonous host plants (e.g. Jammes et al, 2005;Alkharouf et al, 2006;Ithal et al, 2007a;Klink et al, 2007;Szakasits et al, 2009;Barcala et al, 2010;Bagnaresi et al, 2013;Guimaraes et al, 2015), with relatively few studies on monocotyledonous hosts (Kyndt et al, 2012a;Ji et al, 2013;Nguyên et al, 2014). Analysis of the transcriptome of compatible interactions between nematodes and monocotyledonous hosts has so far been limited to studies only on rice.…”
Section: Introductionmentioning
confidence: 99%